Transmission Characteristics Analysis of Optical Fibers - Anilioniene, J. (Elektronika ir Elektrotechnika, 2001)
This work deals with the characteristics of silica fibers. Transmission characteristics of single–mode fiber are briefly explained with electromagnetic theory based on Maxwell’s equation, expressed using a cylindrical co-ordinate. The solutions of equations for an SI fiber with infinite cladding are expressed by Bessel functions in a core region and by Hankel function in a cladding region, respectively. The are obtained cutoff frequency values from the Bessel function zeros. The results the analysis pf mode field of optical fibers is given there.